2018
DOI: 10.1002/1878-0261.12388
|View full text |Cite
|
Sign up to set email alerts
|

A prognostic mRNA expression signature of four 16q24.3 genes in radio(chemo)therapy‐treated head and neck squamous cell carcinoma (HNSCC)

Abstract: Previously, we have shown that copy number gain of the chromosomal band 16q24.3 is associated with impaired clinical outcome of radiotherapy‐treated head and neck squamous cell carcinoma (HNSCC) patients. We set out to identify a prognostic mRNA signature from genes located on 16q24.3 in radio(chemo)therapy‐treated HNSCC patients of the TCGA (The Cancer Genome Atlas, n = 99) cohort. We applied stepwise forward selection using expression data of 41 16q24.3 genes. The resulting optimal Cox‐proportional hazards r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…Deletions in 16q24.2 have been observed frequently in patients with KBG syndrome [33,34], autism spectrum disorder, intellectual disability and congenital renal malformation [30]. Moreover, 16q24.3 alterations aggravate the clinical outcomes of head and neck squamous cell carcinoma [35]. The other RPL-associated CNV identified in this study was duplication of 16p13.3 (7.9 Mb), which was found in 18 cases of miscarriage, but not in the SA cases group.…”
Section: Discussionmentioning
confidence: 52%
“…Deletions in 16q24.2 have been observed frequently in patients with KBG syndrome [33,34], autism spectrum disorder, intellectual disability and congenital renal malformation [30]. Moreover, 16q24.3 alterations aggravate the clinical outcomes of head and neck squamous cell carcinoma [35]. The other RPL-associated CNV identified in this study was duplication of 16p13.3 (7.9 Mb), which was found in 18 cases of miscarriage, but not in the SA cases group.…”
Section: Discussionmentioning
confidence: 52%
“…Based on this, it was shown that the histone variants HIST2H3PS2, HIST2H3D, HIST1H2AI and CENPBD1 were significantly differentially expressed In eukaryotes, the existence of histone variants is based on differences in the primary amino acid sequences, and these variants have different regulatory mechanisms of expression, deposition and genome occupancy (33). Histone variants can alter the structure of nucleosomes and participate in the transcription, replication and repair of DNA (47). CENPBD1 contributes to the formation of the centromere, and may be associated with the prognosis of head and neck squamous cell carcinoma (48).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor stage was assessed using the UICC TNM Classification of Malignant Tumors, 7th edition. HPV status of the patients was determined by p16 INK4a immunohistochemistry in combination with HPV DNA detection as described before [24]. Age, sex, tumor localization, TNM, perineural invasion, extracapsular extension, grading, UICC staging, and HPV status of all patients are provided in Table 1.…”
Section: Methodsmentioning
confidence: 99%